2018
DOI: 10.2196/10676
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Most Visible German Websites on Melanoma Immunotherapy: A Web-Based Analysis

Abstract: Background: Patients diagnosed with melanoma frequently search the internet for treatment

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 32 publications
5
26
0
1
Order By: Relevance
“…Recent studies across multiple specialties have utilized the PEMAT to evaluate online information regarding a wide variety of topics such as diabetes care, cardiovascular disease, and melanoma . Those studies showed that online patient education materials are often inaccurate or far too complicated to understand.…”
mentioning
confidence: 99%
“…Recent studies across multiple specialties have utilized the PEMAT to evaluate online information regarding a wide variety of topics such as diabetes care, cardiovascular disease, and melanoma . Those studies showed that online patient education materials are often inaccurate or far too complicated to understand.…”
mentioning
confidence: 99%
“…German YouTube TM videos as a source of information on cutaneous melanoma: a critical appraisal Editor YouTube TM is an openly accessible video-sharing platform that is increasingly used by melanoma patients to acquire disease-related information. Dissemination of medical information through such a platform may offer valuable opportunities, but also challenges as the quality of unfiltered information posted may be of low scientific quality, 1 or even be misleading. Additionally, the credibility of the providers cannot be verified.…”
mentioning
confidence: 99%
“…T. Steeb, 1,* L. Reinhardt, 2,3 C. G€ orgmayr, 4 H. Weingarten, 4 A. Doppler, 4 J. Br€ utting, 2,3 F. Meier, 2,3 C. Berking, 1 German Skin Cancer Council…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zudem besteht eine Herausforderung darin, geeignete IHA unter den umfangreichen Online-Angeboten zum Melanom ausfi ndig zu machen. In der Regel variieren diese hinsichtlich Qualität und Präzision [10][11][12]…”
unclassified